2019
DOI: 10.3390/app9091954
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Leakage Localization Method Using Multilayer Perceptron Neural Networks in a Pressurized Gas Pipe

Abstract: Leak detection and location in a gas distribution network are significant issues. The acoustic emission (AE) technique can be used to locate a pipeline leak. The time delay between two sensor signals can be determined by the cross-correlation function (CCF), which is a measure of the similarity of two signals as a function of the time delay between them. Due to the energy attenuation, dispersion effect and reverberation of the leakage-induced signals in the pipelines, the CCF location method performs poorly. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…The neurons, represented by the variables/factors used in the analysis, are known as "input layers" and are connected to the "hidden layers" through a neural connection which holds the weights of the hidden layers. The connection of the input and output layers with each neuron of the hidden and output layers is represented by (4) [70]:…”
Section: Multilayer Perceptron Neural Network (Mlp)mentioning
confidence: 99%
“…The neurons, represented by the variables/factors used in the analysis, are known as "input layers" and are connected to the "hidden layers" through a neural connection which holds the weights of the hidden layers. The connection of the input and output layers with each neuron of the hidden and output layers is represented by (4) [70]:…”
Section: Multilayer Perceptron Neural Network (Mlp)mentioning
confidence: 99%
“…Pipeline leak detection techniques can be mainly classified into hardware-based and software-based methods [7][8][9]. Hardware-based methods require the installation of external sensors Various software-based techniques like fuzzy systems [17] support vector machine [18][19][20][21], neural networks [22][23][24][25], statistical [26][27][28] and, transient models [29][30][31], etc. are applied in faults detection studies.…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al [8] presented a method based on theoretical analysis to detect a leak and confirmed that wavelet transform (WT) is an effective tool for determining the source of the leak. Wu et al [9] presented an improved leak localization identification method, which is a combination of two location methods. Xu et al [10] presented a multi-level location method for regional location and precise location.…”
Section: Introductionmentioning
confidence: 99%